New QC-LDPC codes implementation on FPGA platform in Rayleigh fading environment - Farid, Ghani, Prof. Dr.; Abid, Yahya, Dr.; Abdul Kader (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org